Convective heat transfer in a micropolar fluid over an unsteady stretching surface - Prasad, Kerehalli Vinayaka; Vaidya, Hanumesh; Vajravelu, Kuppalapalle (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady boundary layer free convective flow and heat transfer of a viscous incompressible, microploar fluid over a vertical stretching sheet is investigated. The stretching velocity is assumed to vary linearly with the distance along the sheet. Two equal and opposite forces are impulsively applied along the x-axis so that the sheet is stretched, keeping the origin fixed in the micropolar fluid. The transformed highly non-linear boundary layer equations are solved numerically by an implicit finite difference scheme for the transient, state from the initial to the final steady-state.
Keywords: unsteady flow; microrotation; heat transfer; skin friction; Nusselt number; Keller-Box method